Impact of Conception Method on Twin Pregnancy Course and Outcome - Andrijasevic, S.; Dotlic, J.; Aksam, S.; Micic, J.; Terzic, M. (Geburtshilfe und Frauenheilkunde, 2014)
Objective: The aim of the study was to investigate the course and outcomes of twin pregnancies conceived by different methods of assisted reproduction (ART) compared to those conceived spontaneously. Methods: The study involved patients with twin pregnancies who delivered at the Ob/Gyn Clinic of the Clinical Center of Serbia over a period of three years. Patients were differentiated according to method of conception and type of ART. Age, parity, etiology of infertility, pregnancy complications, time of membrane rupture and type of delivery was recorded for each patient. Gestational week at delivery, presentation, birth weight, Apgar score, chorionicity and accompanying disorders were separately recorded for each twin. The data were analyzed statistically. Results: A total of 431 patients were included in the study. Although more twins were conceived by ART, the difference was not statistically significant (p = 0.092). The most common ART procedure was IVF/ICSI (p = 0.001). ART procedures, particularly IVF/ICSI, were significantly correlated with more advanced maternal age, fewer previous pregnancies and delivery by cesarean sections, usually planned (p = 0.001). Preterm membrane rupture was more common after ICSI, but preterm delivery and pregnancy complications were infrequent, irrespective of the method of conception (p = 0.001). ART twins were mostly dichorionic (p = 0.036). Monochorionic twins were conceived either spontaneously or with ICSI. Conception by ART was not correlated with twinsʼ outcome (weight, Apgar score, disorders). Conclusions: ART procedures do not have a negative impact on twin pregnancy course and outcome. Twin pregnancies conceived spontaneously or by ART have similar outcomes.
Keywords: assisted reproductive technology (ART); pregnancy; spontaneous conception; pregnancy outcome; twins